Rethinking sustainability in engineering education: a call for systemic change - Sabri, Omar K. (Frontiers in Education, 2025)
The integration of engineering education with sustainability is a major requirement in overcoming global environmental, social, and economic challenges. The educational approach, however, has not been adequate because it differs or varies from one to another. The article identifies key barriers to the effective teaching and learning of sustainability such as persistence of traditional technical paradigms, lack of interdisciplinary engagement, reluctance to curricular changes, and poor practical exposure. On top of this are the new initiatives such as the accreditation standards, project-based learning, and industry partnership. They have shown a promise toward further enhancement, yet they are still being adopted inconsistently. We take the argument that systemic transformation is needed so that sustainability becomes a fundamental principle of engineering, not just one of its electives. To this discipleship transition, there should be incorporated cross-disciplining curriculum, experiential learning models, and strengthened university-industry collaboration, plus emerging digital technologies. This whole-faculty integrated model will help educates future engineers in a manner that can interpret sustainability challenges and produce positive impacts in their practice.